Dampak Pemanfaatan AI terhadap Pemahaman Konsep Matematika di Era Digital - Muhammad Syarifuddin Rahman (PT. Lontara Digitech Indonesia, 2025)
The use of artificial intelligence (AI) in mathematics learning has continued to grow alongside the rapid digitalization of the education sector. This study aims to analyze the impact of AI utilization on high school students’ understanding of mathematical concepts. The research problem focuses on how the use of AI affects students’ conceptual understanding in mathematics. The method employed is descriptive qualitative research, with data collected through semi-structured interviews, concept-understanding tests, and relevant literature studies. The findings indicate that AI provides positive impacts such as personalized learning, instant feedback, increased motivation, and flexible access to learning resources. Students reported that AI-based systems helped them better comprehend mathematical concepts through adaptive explanations and visualization features. However, the study also identifies negative impacts, including excessive dependence on technology, reduced opportunities for students to learn from mistakes, and a decline in critical thinking skills when solutions are provided instantly by AI. A comparison of learning experiences shows that although AI enhances learning efficiency, conventional methods remain superior in supporting social interaction and group discussion. These findings emphasize that the successful use of AI in mathematics learning heavily depends on balanced implementation strategies and strong pedagogical support from teachers. With proper application, AI can serve as an effective tool to deepen and enrich students’ understanding of mathematical concepts.